THE EFFECT OF DIGITAL ACCOUNTING LITERACY AND ARTIFICIAL INTELLIGENCE (AI) AWARENESS ON THE EFFECTIVENESS OF USING ACCOUNTING INFORMATION SYSTEMS WITH DIGITAL COMPETENCE AS A MODERATING VARIABLE (Study on Accounting Students at Private Universities in Lam - Aida Hariyanti; Isnaini Anniswati Rosyida; Webbyani Kartikasari (Takaza Innovatix Labs Ltd., 2026)
This study aims to analyze the influence of digital accounting literacy and Artificial Intelligence (AI) awareness on the effectiveness of Accounting Information Systems (AIS) use with digital competence as a moderating variable, among accounting students at three private universities in Lamongan Regency (UNISDA, UNISLA, and UMLA). The study used a quantitative explanatory approach with a sample of 77 active students in semesters IV–VIII selected through purposive sampling. Data were collected through an online questionnaire with a Likert scale of 1–5 distributed via Google Form, then analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) assisted by SmartPLS version 4. The results showed that digital accounting literacy had a positive and significant effect on the effectiveness of AIS use (β = 0.299; t = 3.100; p = 0.002), AI awareness had a positive and significant effect (β = 0.445; t = 3.615; p = 0.000), and digital competence had a positive and significant effect (β = 0.347; t = 3.192; p = 0.001). As a moderating variable, digital competence significantly weakened the influence of digital accounting literacy on the effectiveness of AIS use (β = -0.260; t = 2.678; p = 0.007), but significantly strengthened the influence of AI awareness (β = 0.287; t = 2.941; p = 0.003). The research model had strong explanatory power (R² = 0.861) and high predictive relevance (Q² = 0.819). These findings indicate that accounting students' technological readiness is determined by the complex interaction between digital literacy, AI awareness, and digital competence, so that strengthening all three in a balanced manner is important for developing an accounting curriculum in the digital era.